2021
DOI: 10.1016/j.procs.2021.01.308
|View full text |Cite
|
Sign up to set email alerts
|

Managing COVID-19 Crisis using C3HIS Ontology

Abstract: The paper aims to present the C 3 HIS Ontology project, a web based solution for Covid-19 Crisis Health Care Information System. In the health care services, employee skills are a major resource and an essential part of everyday practice and a requirement for all health professions. We aim to prove how using individual profiles based on competencies can make a difference between life and death in times. As the performance assessment is driven by actors competencies we have to put human a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Finally, the C3HIS ontology has been proposed in [154] as a part of a web-based solution for the COVID-19 Crisis Health Care Information System. The authors suggested this ontology to help in managing the crisis in a hospital, prioritizing the COVID-19 services, taking into account the limited resources, professionals working with masks.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the C3HIS ontology has been proposed in [154] as a part of a web-based solution for the COVID-19 Crisis Health Care Information System. The authors suggested this ontology to help in managing the crisis in a hospital, prioritizing the COVID-19 services, taking into account the limited resources, professionals working with masks.…”
Section: Resultsmentioning
confidence: 99%
“…A relationship is the creation of a combination of two or more concepts of an objective relating to data structuring and the completion of action [26]. While some conceptual connections can be expressed using the properties held by concepts, others must be represented using independent relationships [27]. The proposed solution includes some relationships that work together in a conceptual data model (Table 4).…”
Section: Solution Relationshipsmentioning
confidence: 99%
“…In addition, the use of formal semantics is essential for explicit, sharable, and reusable knowledge representation. (Yanga, Cormican, & Yu, 2019) For purposes of illustration, some example ontologies are: educational ontologies, ontologies for cultural heritage data, ontologies for mythology like the Greek one (Syamili & Rekha, 2017), agriculture ontologies, cybersecurity ontologies, biomedical ontologies such as the ontology on genetic disease (Iqtidar, Muzaffar, Qamar, & Rehman, 2017), ontology for diseases of the spine (Lee, Lee, Seo, Yoo, & Kim, 2015); as well as diagnostic ontologies such as ontologies for predictions -like COVID-19 cases, or ontologies for managing the COVID-19 crisis (Sayeb, Jebri, & Ghezala, 2021), and so on.…”
Section: Ontologies In Informatics: a State-of-the-art Reviewmentioning
confidence: 99%